Caracterización socio económica y productiva de la parroquia rural Aláquez, cantón Latacunga, provincia de Cotopaxi, 2022. - Guanoluisa Toapanta, Gabriela Lizeth (2022)
This project was developed in the Aláquez Rural Parish, which belongs to the Latacunga Canton, Cotopaxi Province, located northeast of the Latacunga city, due to the lack of knowledge regarding the socio-economic and productive conditions of the Parish. Previous efforts made by the state and the private sector have been inefficient since there is no evidence of improvement regarding the parish inhabitant dynamics of life and production. So this research has as its primary objective to characterize the social, economic, and productive situation of the Aláquez Rural Parish, for which dimensions, variables, and indicators related to aspects follow: social, economic, and productive. A survey of 64 questions was structured, given to a sample of 400 people scattered in the 29 neighborhoods of the Parish. The greater effectiveness of the investigation KoBoToolbox, free software that does not require constant internet connection, was used to store the data generated from each survey. The following results were obtained. Regarding the social life of the inhabitants of the Aláquez Parish, the highest percentage of the population is young, aged 27 to 36 years, with 100% Ecuadorian nationality, 59% of the population are women, and the predominant level of education is primary with 60%. Also, 98% self-identify as mestizo, and most families are made of 3 to 4 members. The most popular social network is WhatsApp. 63% of the population affirms that their neighborhood has been insecure since recorded house robberies. The economic income of the Aláquez parish inhabitants is based on activities related to agriculture, livestock, forestry, and fishing. 61% of the surveyed population is dedicated to these tasks and relies on them for economic purposes. Despite this, 55% are not satisfied with their economic income due to the low profitability of production due to unfair marketing; not enough means having direct marketing. Due to that, a large part of the population sells the production to intermediaries, who devalue the cost of the products. The productive sector is based on the cultivation of corn, “chocho” and beans and the organization of the Parish is represented by the presidents of each neighborhood. Regarding the productivity of the Aláquez rural parish, 59% have area for agricultural production; 64% have from 1,000 to 5,000 m2 of area for agricultural production; 46% of the population uses the plots to produce crops and animals. Agricultural production is based on corn production with 51%; 68% of the seeds used are their own; 38% of the population mentions that the factor that reduces the harvest is pests and diseases; 71% have sprinkler irrigation; only 12% of the population considers themselves dairy farmers, of which 38% obtained from 1 to 10 liters of milk per day; 58% of the population allocates its products for self-consumption and sale. With the results above, it is recommended that this diagnosis initiate public and private actions to improve the quality of life in the Aláquez Parish residents.